Teaching methods of integrated Naqli and Aqli knowledge for gifted and talented muslim students / Nur Fazidah Asmuje... [et al.] - Asmuje, Nur Fazidah; Abdul Samat, Syukrina Imtiyaz; Abd Razak, Amnah Zanariah; Zainal, Rosita (Universiti Teknologi MARA, Negeri Sembilan, 2018)
Malaysia Education Curriculum mostly adapted from the colonization country since pre-independence. It makes Muslim youngers forget on magnificent of Islam Civilization especially Abbasid Dynasty. By this, the needs of integrating naqli and aqli knowledge in syllabus should be implemented especially among gifted and talented Muslim students. Therefore, this paper focusing on the implementation of integrated naqli and aqli knowledge for Biology's topic as enhancement programmes in gifted and talented curriculum. 56 students from PERMATA Insan who are recognized as gifted and talented students have been participated in this study. The integrated knowledge was conducted through two different approaches including conventional (Method A) and co-teaching (Method B) to identify the suitable teaching method. As result, 47 out of 56 students who were exposed with co-teaching method obtained moderate and high achievement. The students' mark was continuously analysed through t-test to identify the significance difference between two methods. Admittedly, the co-teaching method contributed higher mark during the post-test compared to without co-teaching method. Therefore, co- teaching method is the effective teaching method for integrated naqli and aqli knowledge especially in inheritance topic.